1997
DOI: 10.2466/pr0.1997.80.2.603
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Mathematics Achievement and Attitude toward Mathematics

Abstract: In a study of sex differences in mathematics achievement and attitude toward mathematics, a sample of 278 Standard 10 (Grade 12) students (95 boys and 183 girls) from seven senior secondary schools in the Umtata district of Transkei, South Africa, wrote tests in algebra and geometry and completed an attitude questionnaire. Analysis showed no significant difference between the mean scores of boys and girls in algebra but a significant difference between scores in geometry, with the mean score of boys being grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…The findings are in agreement with other researchers who have shown gender differences in mathematics self-efficacy (Randhawa et al, 1993;Pajares and Miller, 1994;Skaalvik and Rankin, 1994). They are also consistent with the findings on gender differences in mathematics performance, with boys' performance being significantly superior to that of girls (Tate, 1997;Nyangeni and Glencross, 1997;Voyer, 1996). Such gender differences have been attributed, inter alia, to differential mathematics self-efficacy (Pajares and Miller, 1994;Randhawa et al, 1993), which is a good predictor of performance in mathematics (Eshel and Kurman, 1991;Simpson et al, 1996).…”
Section: Discussionsupporting
confidence: 92%
“…The findings are in agreement with other researchers who have shown gender differences in mathematics self-efficacy (Randhawa et al, 1993;Pajares and Miller, 1994;Skaalvik and Rankin, 1994). They are also consistent with the findings on gender differences in mathematics performance, with boys' performance being significantly superior to that of girls (Tate, 1997;Nyangeni and Glencross, 1997;Voyer, 1996). Such gender differences have been attributed, inter alia, to differential mathematics self-efficacy (Pajares and Miller, 1994;Randhawa et al, 1993), which is a good predictor of performance in mathematics (Eshel and Kurman, 1991;Simpson et al, 1996).…”
Section: Discussionsupporting
confidence: 92%
“…Negative attitudes and beliefs about ES can result in reduced interest, which in turn impedes ES learning. In a study of Standard 10 students in South Africa, [16] observed that the correlation between attitudes towards mathematics and mathematics scores is signi® cant but low. A discussion on the role of non-cognitive issues and their eå ects on statistics learning is available in [6].…”
Section: Interestmentioning
confidence: 96%
“…The performance of boys in arithmetic was sig-boys outscore girls, in most teacher-assigned mathematics, either girls outperform boys or there are no sex differences (Benbow, 1992;Randhawa, Beamer & Lundberg, 1993;Gallagher & De Lisi, 1994;Macleod, 1995). Nyangeni and Glencross (1997) in their study of South African Standard 10…”
mentioning
confidence: 94%
“…In a study of 450 Standards 9 and 10 South African students' understanding of mathematical concepts, no sex differences were observed (Sibaya, Sibaya, & Mugisha, 1996). Similarly, Nyangeni, and Glencross (1997) reported that, in 278 South African Standard 10 mathematics students' achievement in algebra and geometry, there were no sex differences in performance in algebra. Both North American and British litera-ture, in the main, indicate that there were no sex differences in mathematics performance in primary and junior secondary school (Macleod, 1995).…”
mentioning
confidence: 98%